Development of Basic Electricity and Electronics Practicum Jobsheet for Students of Electric Power Installation Engineering Expertise at SMK Negeri 3 Boyolangu - Septyawan, Eggy Catur; Putranto, Hari; Wibawanto, Slamet (Letters in Information Technology Education (LITE), 2023)
This development research aims to develop printed teaching materials in the form of practicum job sheets to assist the learning process of basic electricity and electronics by the 2013 curriculum. Research and Development is a research model used to develop existing products. The development model in this study is the Sugiyono model. This development stage begins with looking for potential problems, collecting data, designing products, validating designs, product trials, design revisions, product testing, product revisions, usage trials, and product revisions, and ends with mass production. The development of this teaching material has met the criteria for proper use with the results obtained from experts with a validation expert value of 93.8 percent; product trial results with an average value of 90.4%, and usage trial results with an average value of 93.6 percent.